Isotopic niche variation in Tasmanian devils Sarcophilus harrisii with progression of devil facial tumor disease. Issue 12 (6th June 2021) - Bell, Olivia; Jones, Menna E.; Cunningham, Calum X.; Ruiz‐Aravena, Manuel; Hamilton, David G.; Comte, Sebastien; Hamede, Rodrigo K.; Bearhop, Stuart; McDonald, Robbie A.
Abstract: Devil facial tumor disease (DFTD) is a transmissible cancer affecting Tasmanian devils Sarcophilus harrisii . The disease has caused severe population declines and is associated with demographic and behavioral changes, including earlier breeding, younger age structures, and reduced dispersal and social interactions. Devils are generally solitary, but social encounters are commonplace when feeding upon large carcasses. DFTD tumors can disfigure the jaw and mouth and so diseased individuals might alter their diets to enable ingestion of alternative foods, to avoid conspecific interactions, or to reduce competition. Using stable isotope analysis (δ 13 C and δ 15 N) of whiskers, we tested whether DFTD progression, measured as tumor volume, affected the isotope ratios and isotopic niches of 94 infected Tasmanian devils from six sites in Tasmania, comprising four eucalypt plantations, an area of smallholdings and a national park. Then, using tissue from 10 devils sampled before and after detection of tumors and 8 devils where no tumors were detected, we examined whether mean and standard deviation of δ 13 C and δ 15 N of the same individuals changed between healthy and diseased states. δ 13 C and δ 15 N values were generally not related to tumor volume in infected devils, though at one site, Freycinet National Park, δ 15 N values increased significantly as tumor volume increased. Infection with DFTD was not associated with significant changes in the mean or standard deviation of δ 13 C and δ 15 N values in individual devils sampled before and after detection of tumors. Our analysis suggests that devils tend to maintain their isotopic niche in the face of DFTD infection and progression, except where ecological conditions facilitate a shift in diets and feeding behaviors, demonstrating that ecological context, alongside disease severity, can modulate the behavioral responses of Tasmanian devils to DFTD. Abstract : Tasmanian devils generally maintain their isotopic niche in the face of infection and progression of devil facial tumor disease. The exception was where ecological conditions facilitated a shift in diets and feeding behaviors, such as at Freycinet National Park. Ecological context, alongside disease severity, can modulate the behavioral responses of Tasmanian devils to DFTD. ​